Oxidation and peroxidation in the uvea of the rabbit eyes with experimental uveitis and ocular hypertension (Ukrainian Journal of Ophthalmology, 2025)
Background. The role of metabolic changes in the anterior eye tissues in the pathogenesis of uveal inflammation in patients with elevated intraocular pressure has been studied poorly. Of particular interest, in this respect, are free radical mechanisms, which can be a trigger of oxidant stress and cause damage to cell membranes in ocular tissues.Purpose. To study the activity of pro-oxidant enzymes and  levels of lipid peroxidation products in the uvea tissues in the rabbits with experimental anterior non-infectious uveitis against the background of ocular hypertension. Material and Methods. Forty-one rabbits were divided into 4 study groups. Group 1: 10 animals with experimental ocular hypertension; group 2: 10 animals with experimental allergic uveitis; group 3: 12 animals with ocular hypertension and allergic uveitis; and group 4: 9 intact animals serving as controls. To simulate ocular hypertension in the groups 1 and 3, the animals were made a single 0.1 ml injection of 0.3% carbomer into the anterior chamber. The tissues of the uvea and the aqueous humour were studied biochemically. We estimated the activity of pro-oxidant enzymes, NADPH oxidase and xanthine oxidase, and the content of lipid peroxides: malonic dialdehyde and diene conjugates. The data of the experimental studies were processed using parametric statistical tests with an SPSS package and Statistica 5.5Results. The activity of pro-oxidants enzymes was increased in all uvea tissues in all study groups; the maximal NADPH oxidase and xanthine oxidase activity was in the animals with both ocular hypertension and uveitis. The NADPH oxidase and xanthine oxidase activity was increased by 51.1% and 63.9% (р
Keywords: ocular hypertension; uveitis; oxidation; lipid peroxidation; malonic dialdehyde; diene conjugates; rabbits